2004
DOI: 10.1186/1471-2377-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying fatigue: a voxel-based morphometric study of chronic fatigue syndrome

Abstract: Background: Fatigue is a crucial sensation that triggers rest, yet its underlying neuronal mechanisms remain unclear. Intense long-term fatigue is a symptom of chronic fatigue syndrome, which is used as a model to study the mechanisms underlying fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
162
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 26 publications
8
162
3
1
Order By: Relevance
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 86%
“…Although the cause of CFS remains unknown, altered central nervous system (CNS) function is believed to play an important role,4 including altered perception of fatigue and pain, deficits in the cognitive functions of concentration and memory, mood changes of depression and anxiety, and sleep disturbance 1. Accordingly, neuroimaging studies have investigated possible brain changes associated with CFS 5, 6, 7, 8. However, most of the previous neuroimaging studies were cross sectional comparisons of differences between CFS patients and normal controls (NCs) except one longitudinal study that examined white matter (WM) hyperintensities, cerebral blood and cerebrospinal fluid (CSF) flows in scans 1 year apart 9…”
mentioning
confidence: 99%
“…This model is consistent with other fatiguing disorders as well, because of their pathogenesis in the cortico-striato-thalamic circuit. Brain-imaging studies revealed involvement of the prefrontal cortex in patients with chronic fatigue syndrome [36], and in the prefrontal cortex and thalamus in patients with fatigue associated with multiple sclerosis [37]. Abnormal metabolic findings have also been reported in the prefrontal cortex and basal ganglia (putamen) in patients with fatigue and multiple sclerosis [38].…”
Section: Discussionmentioning
confidence: 96%
“…Using these methods, both global searches (with no a priori hypotheses) and directed searches were performed in regions predicted to show anatomical changes. Based on regions shown to have anatomical changes in other voxel-based morphometry studies of chronic pain conditions (Apkarian et al, 2004;Schmidt-Wilcke et al, 2005 and stress-related disorders, including chronic fatigue syndrome and post-traumatic stress disorder (Villarreal et al, 2002;Okada et al, 2004;Chen et al, 2006), directed searches were performed in anterior, mid, and posterior cingulate cortex, insular cortex, dorsolateral prefrontal cortex, medial prefrontal cortex, and the parahippocampal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in brain morphology have been described in chronic pain conditions (Apkarian et al, 2004;Schmidt-Wilcke et al, 2005, chronic fatigue syndrome (Okada et al, 2004;de Lange et al, 2005), and posttraumatic stress disorder (Villarreal et al, 2002;Corbo et al, 2005;Chen et al, 2006). Because fibromyalgia shares commonalities with these disorders, we hypothesized that fibromyalgia might be associated with neuroanatomical abnormalities as well.…”
Section: Introductionmentioning
confidence: 99%